The Phantom of the Opera: An Horror Classic - Francis, Pauline (Evans Brothers Ltd, 2005)
A young singer, Christine Daae, makes a triumphant debut at the Opera - and then disappears. What has happened to her, and could the mysterious Opera ghost be to blame? Christine's lover, Raoul de Chagny, spies a mysterious stranger shadowing her and decides to follow...
Keywords: Scary